Physical and technical demands of elite beach volleyball according to playing position and gender - Natali, S.; Ferioli, D.; La Torre, A.; Bonato, M. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Beach volleyball is a team sport played by two teams of two players on a sand court divided by a net. To date, research has mainly focused on male beach volleyball players. Therefore, the aim of this study was to assess work-rest ratio and physical actions between males and females according to their role. METHODS: Forty-two elite beach volley players (24 males and 18 females) were filmed during 12 beach volleyball matches of the Swatch Major Series 2016 of the beach volleyball World Tour in Porec in (Croatia). Duration of point rallies, work rest ratio and the number of jumps and hits performed by the players according to their role (blockers and defenders) were recorded. RESULTS: Twenty-one teams (12 males and 9 females) were recorded during a total of 12 matches comprising 11 sets for males and 9 sets for females. Males scored a total of 428 points whereas females scored 440 points. Un-paired t-test did not show significant differences between males and females. Two-way analysis of variance showed a significant difference in the jumps performed between blockers and defenders and not between males and females. No significant differences in the other variables were detected. CONCLUSIONS: The present study provides new inside into female beach volleyball matches, giving preliminary normative data. Technical and physical aspects of beach volleyball performance appear not to be influenced by gender and to be only partially different according to playing positions. These results should be considered during the daily training scheduling.